2020
DOI: 10.1097/qad.0000000000002411
|View full text |Cite
|
Sign up to set email alerts
|

Timing of and factors associated with HIV disclosure among perinatally infected children in rural Zambia

Abstract: Objective: This study was conducted to understand the process of disclosure among HIV-infected children receiving care in rural Zambia. Design: Cross-sectional and longitudinal analyses were conducted within an ongoing clinical cohort study of HIV-infected children receiving care in Macha, Zambia from 2007 to 2016. Methods: Children receiving HIV care were enrolled into the cohort study and assessed every 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…One of the contributors to this lack of adherence may be that some adolescents have a poor understanding of their illness and the availability of medications to suppress the virus. Our review of this issue showed that in our own situation, the median age of disclosure of the fact that the child had HIV was at 9 years of age, though only 76% of those aged 13-15 years had been given full disclosure by the caregiver (Sutcliffe et al, 2020). We cannot expect children and adolescents to take control of and manage their chronic disease if they do not even know they have it!…”
mentioning
confidence: 85%
“…One of the contributors to this lack of adherence may be that some adolescents have a poor understanding of their illness and the availability of medications to suppress the virus. Our review of this issue showed that in our own situation, the median age of disclosure of the fact that the child had HIV was at 9 years of age, though only 76% of those aged 13-15 years had been given full disclosure by the caregiver (Sutcliffe et al, 2020). We cannot expect children and adolescents to take control of and manage their chronic disease if they do not even know they have it!…”
mentioning
confidence: 85%
“…As children living with HIV can grow up into adolescence and adulthood if they remain adherent to treatment and for this, they need to be informed about their situation. Disclosure of a child’s HIV status is of clinical importance in children as it will help them comply with the HIV treatment regimen [ 6 , 7 ]. That is why the World Health Organization (WHO) recommends that children should be informed of their HIV status before the age of 12 years [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches to the disclosure of HIV status have been described [ 6 ]. Each of these places particular emphasis on the role of parents and health care workers (HCWs) in disclosing to children [ 17 , 18 , 19 ] without exploring the potential role that other individuals (peers,…) might play in the process of disclosure [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…A cohort study in rural Zambia indicated that 89.5% of children were first reported to have partial disclosure at a median age of 7.4 years. Reasons for non-disclosure included caregivers considering the child to be too young, feeling scared or not knowing how to tell the child (10) . Furthermore, there is no consensus on who will disclose, whether it will be the parents or the professionals, which implies low disclosure rates in countries such as those in sub-Saharan Africa (5) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, evidence-based interventions and protocols are needed to support caregivers (8,10) . Additionally, there is a lack of national and international evidence about the conduct of the disclosure follow-up.…”
Section: Introductionmentioning
confidence: 99%